Identification of α‐fetoprotein‐specific T‐cell receptors for hepatocellular carcinoma immunotherapy. Issue 2 (12th June 2018) - Zhu, Wei; Peng, Yibing; Wang, Lan; Hong, Yuan; Jiang, Xiaotao; Li, Qi; Liu, Heping; Huang, Lei; Wu, Juan; Celis, Esteban; Merchen, Todd; Kruse, Edward; et al.
Abstract : Hepatocellular carcinoma (HCC) is the major form of liver cancer for which there is no effective therapy. Genetic modification with T‐cell receptors (TCRs) specific for HCC‐associated antigens, such as α‐fetoprotein (AFP), can potentially redirect human T cells to specifically recognize and kill HCC tumor cells to achieve antitumor effects. In this study, using lentivector and peptide immunization, we identified a population of cluster of differentiation 8 (CD8) T cells in human leukocyte antigen (HLA)‐A2 transgenic AAD mice that recognized AFP158 epitope on human HCC cells. Adoptive transfer of the AFP158 ‐specific mouse CD8 T cells eradicated HepG2 tumor xenografts as large as 2 cm in diameter in immunocompromised nonobese diabetic severe combined immunodeficient gamma knockout (NSG) mice. We then established T‐cell hybridoma clones from the AFP158 ‐specific mouse CD8 T cells and identified three sets of paired TCR genes out of five hybridomas. Expression of the murine TCR genes redirected primary human T cells to bind HLA‐A2/AFP158 tetramer. TCR gene‐engineered human T (TCR‐T) cells also specifically recognized HLA‐A2 + AFP + HepG2 HCC tumor cells and produced effector cytokines. Importantly, the TCR‐T cells could specifically kill HLA‐A2 + AFP + HepG2 tumor cells without significant toxicity to normal primary hepatocytes in vitro . Adoptive transfer of the AFP‐specific TCR‐T cells could eradicate HepG2 tumors in NSG mice. Conclusion: We have identified AFP‐specific murine TCR genes that can redirect human T cells to specifically recognize and kill HCC tumor cells, and those AFP158 ‐specific TCRs have a great potential to engineer a patient's autologous T cells to treat HCC tumors. (Hepatology 2018).